Bosnian St. Louis between two worlds - McCarthy, Patrick 1961- (Missouri Historical Society Press, 2022)
"Bosnian St. Louis is a warm and richly illustrated tribute to an unlikely immigrant success story in America's heartland. In the 1990s, Bosnia and Herzegovina was rocked by brutal warfare and systematic genocide, leading to a mass exodus from the Balkan nation. Starting in 1993, thousands of these displaced Bosnians found a welcoming new home in an unexpected place: St. Louis, Missouri, where today the Bosnian population exceeds 60,000. Bosnian St. Louis tells the story of how these resettled immigrants took root in a new home and quickly reshaped the image of their adopted city. Using first-hand accounts from members of St. Louis's Bosnian community, Patrick McCarthy and Akif Cogo explore how an event of global significance became the lived reality of the refugees who came to St. Louis and who, in the ensuing years, have had a profound effect on the character of the city they now call home. The city's resettled Bosnians quickly established themselves as a positive local presence, bringing with them tight-knit families, a strong work ethic, and a rich cultural heritage. Tragedy and sorrow created the Bosnian community in St. Louis, but, as this book makes clear, new beginnings and opportunities are building a brighter future for the city's Bosnians and for all those who call them neighbors and friends. Illustrated with nearly one hundred images and featuring an introduction from acclaimed writer and Bosnian immigrant Aleksandar Hemon, Bosnian St. Louis is a groundbreaking account of a vast refugee resettlement in a single US city and a testament to how that resettlement has changed that city forever"--
Includes index
Keywords: Geschichte 1993-; Einwanderer; Bosnier; Saint Louis, Mo.; Bosnian Americans / Missouri / Saint Louis / History; Bosnians / Illinois / Missouri / Saint Louis / History; Refugees / Missouri / Saint Louis / Social conditions; Yugoslav War, 1991-1995 / Refugees; Saint Louis (Mo.) / Ethnic relations; Saint Louis (Mo.) / History; HISTORY / United States / State & Local / Midwest (IA, IL, IN, KS, MI, MN, MO, ND, NE, OH, SD, WI); HISTORY / General; Bosnian Americans; Bosnians; Ethnic relations; Refugees; Refugees / Social conditions; Missouri / Saint Louis; 1991-1995; History